Expression and clinical significance of CD31, CD34, and CD105 in pulmonary ground glass nodules with different vascular manifestations on CT - Guo, Chen-ran; Han, Rui; Xue, Feng; Xu, Lin; Ren, Wan-gang; Li, Meng; Feng, Zhen; Hu, Ben-chuang; Peng, Zhong-min (Frontiers in Oncology, 2022)
Blood vessel passage on CT exerts a vital part in early diagnosis as well as treatment of carcinoma of the lungs. Intratumoral micro-vascular density (iMVD) has gradually become the focus of research on biological behavior, appearance as well as evolution of malignant tumors nowadays. The paper aims to verify whether there is a correlation between the iMVD and the vascular morphology of ground-glass nodules (GGNs). 109 patients with pulmonary GGN were classified into three groups (Ⅰ,Ⅱ,Ⅲ) according to the vascular morphology on CT, and their expression of CD31, CD34 and CD105 labeled iMVD was detected by streptoavidin-biotin method, statistical analyzing the iMVD-values of each group. The expression of CD31, CD34 and CD105 in different lung tissues was significantly different, with remarkably higher iMVD in lung cancer tissues than in adjacent normal lung tissues. In the imaging sort of type I, II and III according to the way of vascular passage, the iMVD expression of CD31, CD34 and CD105 was significantly different between groups. These data suggest that the presence as well as the abnormal morphology of vessels seen within GGNs indicates the occurrence and progression of lung cancer in pathology. It offers a strong theoretical foundation for early diagnosis of carcinoma of the lungs, thus providing a more precise clinical diagnosis and prognosis of early stage lung cancer.